Peace negotiations between Russia and Latvia in 1920: Premises, key issues, and outcomes - Yu. L. Mikhailova (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The conclusion of the Peace Treaty between Latvia and the RSFSR on August 11, 1920 marked an important stage both in the process of international recognition of Latvia and in the normalization of international relations in the region in general, and charted a new course of the foreign policy of the Soviet state. On the basis of a wide range of archival sources (transcripts of the plenary meetings of the RSFSR and Latvia delegations, the meetings minutes of the Soviet-Latvian boundary commission, etc.), as well as recent Russian and foreign historical researches, the paper examines a set of issues related to the conclusion of the Treaty. The key issues that predetermined the agenda of the Soviet-Latvian peace negotiations included border demarcation, the exchange of war prisoners, the return of property evacuated to Russia, the return of refugees and the establishment of procedures for citizenship option. The author notes that the issue of border delimitation and demarcation was one of the most controversial and painful during the negotiations. The ethnographic principle for future borders was inextricably linked with economic and military-strategic considerations. The author examines territorial concessions made by the RSFSR to Latvia and concludes that they served as a demonstration of the Soviet Russia readiness to take into account the territorial claims of the Baltic republics, which allowed it to achieve peace in the region and fix new borders, as well as to establish trade relations indispensable for the survival of a young Soviet state during the Civil War. At the same time, the Soviet representatives took a hard line on compensations for the damage caused during hostilities and the return of property evacuated from Latvia. The author concludes that the Soviet-Latvian treaty and similar treaties with other Baltic states not only enabled the establishment of a new balance of power in the East Baltic region for the interwar period and laid the foundation for the Soviet foreign policy towards the Baltic republics, but also served as a vivid example of realization of ‘the right of self-determination of peoples up to secession’. Finally, these treaties became one of the means to break the diplomatic isolation of Soviet Russia.